Prospective English Teachers' Perspective on the Teaching Materials of Translation as Profession Subject - Masitowarni Siregar; Nora Ronita Dewi; Safrida Lubis (Randwick International of Education and Linguistics Science Journal, 2020)
Universally, the need for translator keeps increasing. This is due to the wider contact globally among countries. More common issue are also faced by countries in general. Therefore translation is required to transfer the meaning of how one issue is handled in one country and how is it in another. Based on these universities try to accommodate these needs by providing the subject of Translation in the curriculum. The objective of this study is to find out the prespective of prospective English teachers on the materials needed for Translation as Profession Subject.This research utilized Research and Development design implemented in 3 stages. First stage is identifying existing situation. The second stage is developing the material. The third stage validation of the product. The result of the validation shows that the book is valid with the average score is 4.30. The material was uploaded to Faculty of Languages and Arts Online System to be use din the teaching and learning process.